CN116835621A - Spherical step hole alumina and preparation method and application thereof - Google Patents

Spherical step hole alumina and preparation method and application thereof Download PDF

Info

Publication number
CN116835621A
CN116835621A CN202310730494.8A CN202310730494A CN116835621A CN 116835621 A CN116835621 A CN 116835621A CN 202310730494 A CN202310730494 A CN 202310730494A CN 116835621 A CN116835621 A CN 116835621A
Authority
CN
China
Prior art keywords
powder
alumina
sphere
pore
boehmite
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Granted
Application number
CN202310730494.8A
Other languages
Chinese (zh)
Other versions
CN116835621B (en
Inventor
李慧胜
徐景东
艾子龙
曾晓霖
徐人威
马小波
王娇红
孟祥东
王美玲
陈伟敏
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Sinochem Quanzhou Petrochemical Co Ltd
Sinochem Quanzhou Energy Technology Co Ltd
Original Assignee
Sinochem Quanzhou Petrochemical Co Ltd
Sinochem Quanzhou Energy Technology Co Ltd
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Sinochem Quanzhou Petrochemical Co Ltd, Sinochem Quanzhou Energy Technology Co Ltd filed Critical Sinochem Quanzhou Petrochemical Co Ltd
Priority to CN202310730494.8A priority Critical patent/CN116835621B/en
Publication of CN116835621A publication Critical patent/CN116835621A/en
Application granted granted Critical
Publication of CN116835621B publication Critical patent/CN116835621B/en
Active legal-status Critical Current
Anticipated expiration legal-status Critical

Links

Classifications

    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01F—COMPOUNDS OF THE METALS BERYLLIUM, MAGNESIUM, ALUMINIUM, CALCIUM, STRONTIUM, BARIUM, RADIUM, THORIUM, OR OF THE RARE-EARTH METALS
    • C01F7/00—Compounds of aluminium
    • C01F7/02—Aluminium oxide; Aluminium hydroxide; Aluminates
    • B—PERFORMING OPERATIONS; TRANSPORTING
    • B01—PHYSICAL OR CHEMICAL PROCESSES OR APPARATUS IN GENERAL
    • B01J—CHEMICAL OR PHYSICAL PROCESSES, e.g. CATALYSIS OR COLLOID CHEMISTRY; THEIR RELEVANT APPARATUS
    • B01J21/00—Catalysts comprising the elements, oxides, or hydroxides of magnesium, boron, aluminium, carbon, silicon, titanium, zirconium, or hafnium
    • B01J21/02—Boron or aluminium; Oxides or hydroxides thereof
    • B01J21/04—Alumina
    • B—PERFORMING OPERATIONS; TRANSPORTING
    • B01—PHYSICAL OR CHEMICAL PROCESSES OR APPARATUS IN GENERAL
    • B01J—CHEMICAL OR PHYSICAL PROCESSES, e.g. CATALYSIS OR COLLOID CHEMISTRY; THEIR RELEVANT APPARATUS
    • B01J23/00—Catalysts comprising metals or metal oxides or hydroxides, not provided for in group B01J21/00
    • B01J23/002—Mixed oxides other than spinels, e.g. perovskite
    • B—PERFORMING OPERATIONS; TRANSPORTING
    • B01—PHYSICAL OR CHEMICAL PROCESSES OR APPARATUS IN GENERAL
    • B01J—CHEMICAL OR PHYSICAL PROCESSES, e.g. CATALYSIS OR COLLOID CHEMISTRY; THEIR RELEVANT APPARATUS
    • B01J23/00—Catalysts comprising metals or metal oxides or hydroxides, not provided for in group B01J21/00
    • B01J23/70—Catalysts comprising metals or metal oxides or hydroxides, not provided for in group B01J21/00 of the iron group metals or copper
    • B01J23/76—Catalysts comprising metals or metal oxides or hydroxides, not provided for in group B01J21/00 of the iron group metals or copper combined with metals, oxides or hydroxides provided for in groups B01J23/02 - B01J23/36
    • B01J23/84—Catalysts comprising metals or metal oxides or hydroxides, not provided for in group B01J21/00 of the iron group metals or copper combined with metals, oxides or hydroxides provided for in groups B01J23/02 - B01J23/36 with arsenic, antimony, bismuth, vanadium, niobium, tantalum, polonium, chromium, molybdenum, tungsten, manganese, technetium or rhenium
    • B01J23/85—Chromium, molybdenum or tungsten
    • B01J23/88—Molybdenum
    • B01J23/883—Molybdenum and nickel
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01F—COMPOUNDS OF THE METALS BERYLLIUM, MAGNESIUM, ALUMINIUM, CALCIUM, STRONTIUM, BARIUM, RADIUM, THORIUM, OR OF THE RARE-EARTH METALS
    • C01F7/00—Compounds of aluminium
    • C01F7/02—Aluminium oxide; Aluminium hydroxide; Aluminates
    • C01F7/021—After-treatment of oxides or hydroxides
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01F—COMPOUNDS OF THE METALS BERYLLIUM, MAGNESIUM, ALUMINIUM, CALCIUM, STRONTIUM, BARIUM, RADIUM, THORIUM, OR OF THE RARE-EARTH METALS
    • C01F7/00—Compounds of aluminium
    • C01F7/02—Aluminium oxide; Aluminium hydroxide; Aluminates
    • C01F7/44—Dehydration of aluminium oxide or hydroxide, i.e. all conversions of one form into another involving a loss of water
    • C01F7/441—Dehydration of aluminium oxide or hydroxide, i.e. all conversions of one form into another involving a loss of water by calcination
    • C—CHEMISTRY; METALLURGY
    • C10—PETROLEUM, GAS OR COKE INDUSTRIES; TECHNICAL GASES CONTAINING CARBON MONOXIDE; FUELS; LUBRICANTS; PEAT
    • C10G—CRACKING HYDROCARBON OILS; PRODUCTION OF LIQUID HYDROCARBON MIXTURES, e.g. BY DESTRUCTIVE HYDROGENATION, OLIGOMERISATION, POLYMERISATION; RECOVERY OF HYDROCARBON OILS FROM OIL-SHALE, OIL-SAND, OR GASES; REFINING MIXTURES MAINLY CONSISTING OF HYDROCARBONS; REFORMING OF NAPHTHA; MINERAL WAXES
    • C10G45/00—Refining of hydrocarbon oils using hydrogen or hydrogen-generating compounds
    • C10G45/02—Refining of hydrocarbon oils using hydrogen or hydrogen-generating compounds to eliminate hetero atoms without changing the skeleton of the hydrocarbon involved and without cracking into lower boiling hydrocarbons; Hydrofinishing
    • C10G45/04—Refining of hydrocarbon oils using hydrogen or hydrogen-generating compounds to eliminate hetero atoms without changing the skeleton of the hydrocarbon involved and without cracking into lower boiling hydrocarbons; Hydrofinishing characterised by the catalyst used
    • B—PERFORMING OPERATIONS; TRANSPORTING
    • B01—PHYSICAL OR CHEMICAL PROCESSES OR APPARATUS IN GENERAL
    • B01J—CHEMICAL OR PHYSICAL PROCESSES, e.g. CATALYSIS OR COLLOID CHEMISTRY; THEIR RELEVANT APPARATUS
    • B01J2523/00—Constitutive chemical elements of heterogeneous catalysts
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2006/00—Physical properties of inorganic compounds
    • C01P2006/12—Surface area
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2006/00—Physical properties of inorganic compounds
    • C01P2006/14—Pore volume
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2006/00—Physical properties of inorganic compounds
    • C01P2006/16—Pore diameter
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2006/00—Physical properties of inorganic compounds
    • C01P2006/16—Pore diameter
    • C01P2006/17—Pore diameter distribution

Landscapes

  • Chemical & Material Sciences (AREA)
  • Organic Chemistry (AREA)
  • Engineering & Computer Science (AREA)
  • Chemical Kinetics & Catalysis (AREA)
  • Materials Engineering (AREA)
  • Life Sciences & Earth Sciences (AREA)
  • Geology (AREA)
  • Inorganic Chemistry (AREA)
  • Oil, Petroleum & Natural Gas (AREA)
  • General Chemical & Material Sciences (AREA)
  • Catalysts (AREA)

Abstract

The invention discloses a spherical step hole alumina, a preparation method and application thereof, wherein the average hole diameter of the alumina is increased stepwise from the center to the outer surface of a sphere along the radial direction of the sphere, and the surface layer contains a large hole structure with a certain proportion of more than 100 nm. According to the invention, through combining pseudo-boehmite raw materials with different grain sizes and a template agent, the pore diameters of the inner part and the surface layer of the spherical alumina are flexibly regulated and controlled, and finally the pore diameters of the alumina become larger from the center of the sphere to the outer surface to form an open step-shaped pore structure, so that the diffusion performance of the alumina is improved, and the alumina is suitable for being used as a residual oil hydrogenation catalyst carrier.

Description

Spherical step hole alumina and preparation method and application thereof
Technical Field
The invention belongs to the technical field of catalysts, and particularly relates to spherical step hole alumina, and a preparation method and application thereof.
Background
With the deepening of the heavy and inferior degree of crude oil, environmental regulations are increasingly strict, and the adoption of hydrogenation technology to treat residual oil can not only convert heavy oil into light oil products and improve the utilization rate of crude oil, but also reduce environmental pollution and meet the requirements of environmental regulations. Therefore, the residuum hydrotreating technology becomes the first technology for processing heavy oil by various refining enterprises.
Residuum hydrogenation techniques generally include fixed bed, moving bed, ebullated bed, slurry bed, and like process technologies. Among them, the fixed bed residuum hydrogenation technology has higher maturity and the most widely used. In fixed bed residuum hydroprocessing techniques, an upflow reactor (UFR) may be provided before the fixed bed reactor to extend the unit run length. In the upflow reactor, the mixture of the raw oil and the hydrogen flows upwards from the bottom of the reactor to pass through the catalyst bed layer, so that the whole catalyst bed layer is in a micro-expansion state, the pressure drop of the reactor is small, and meanwhile, impurity metals (mainly Ni and V), sulfur, nitrogen and the like in the raw oil can be effectively removed, the downstream fixed bed catalyst is protected, the performance of the whole catalyst is fully exerted, and the running period of the device is prolonged. It is generally believed that the upflow residuum hydrogenation catalyst is more suitable for smaller particle size spheres.
Most of the metal impurities in the residuum mainly exist in macromolecular compounds such as colloid, asphaltene and the like, the compounds have complex structures and large molecular sizes, and are difficult to diffuse in catalyst pore channels, so that the residuum hydrotreating process is a typical internal diffusion control process, and coke and removed metal are deposited on the surface of the catalyst and in the pore channels. In order to avoid rapid deactivation of the catalyst caused by plugging of deposited metal and coke in the pores of the catalyst surface, the upflow residuum hydrogenation catalyst is required to have an excellent pore structure, the catalyst surface layer of which should have macropores to satisfy diffusion and mass transfer of macromolecular compounds such as asphaltene, and the inside of which has a mesopore structure to provide a sufficient active surface, thereby improving the reactivity of the catalyst and prolonging the service life of the catalyst.
Patent CN 1665907A discloses an upflow hydrogenation catalyst, wherein a carrier of the catalyst consists of alumina, the pore volume is 0.6-1.1 mL/g, and the specific surface area is 110-190 m 2 And/g, wherein the pores with the diameter of more than 1000 angstroms are less than 35 percent, the peak pore diameter of the nitrogen desorption method is 80-140 angstroms, the shape of the catalyst is spherical or elliptical, and the granularity is about 0.1 inch (about 2.5 mm). The catalyst has smaller average pore diameter and is similar to the catalyst prepared by the U.S. Pat. No. 5472928Compared with the prior art, the catalyst has higher hydrodesulfurization activity and lower hydrodemetallization activity. In the hydrogenation of heavy oils, the heavy feedstock is contacted with a catalyst prepared according to US 5472928 under hydrodemetallization conditions, and the product is then hydrodesulfurized by contacting the catalyst. The catalyst is suitable as a hydrodesulfurization catalyst, and the service life of the catalyst can be prolonged only by the prior graded hydrodemetallization catalyst, so that the catalyst is not suitable for being singly used in an upflow reactor.
US patent 4448896 discloses an alumina carrier with smooth pore canal and its preparation method, which uses pseudo-boehmite as raw material and carbon black powder as pore-enlarging agent, and the alumina carrier is obtained by kneading, extruding, drying and roasting. The defect is that a small amount of carbon black powder is added, so that 'ink bottle' -shaped holes are easy to form, and smooth pore channels are difficult to form; too much carbon black powder can significantly reduce the carrier strength.
Patent CN 104646005a discloses a catalyst with an open "horn-shaped" pore structure and a preparation method, wherein the pore of the catalyst carrier is continuously enlarged from the center to the outer surface of the particle, and the average pore diameter is 19.0-30.0 nm. The method can alleviate the blocking problem of the catalyst orifice to a certain extent, but the catalyst surface layer lacks macropores, the improvement on the catalyst diffusion performance is limited, and macromolecular reaction substances such as asphaltene still have difficulty in penetrating into the center position of the catalyst particles.
Disclosure of Invention
Aiming at the defects of the prior art, the invention provides the step hole alumina and the preparation method thereof, the step hole alumina has the characteristics of large hole volume, large aperture and stepwise expansion of pore channels from inside to outside, and meanwhile, the surface layer of the step hole alumina contains a macroporous structure with a certain proportion of more than 100nm, so that the diffusion performance is excellent, and the step hole alumina can be used as a catalyst carrier, in particular to an up-flow type residual oil hydrotreating catalyst carrier.
In order to achieve the above purpose, the invention adopts the following technical scheme:
a spherical step hole alumina with a pore volume of 0.6-1.6 mL/g and a specific surface area of 80-250 m by mercury intrusion method 2 The average pore diameter is increased stepwise from the center to the outer surface along the radial direction of the sphere, wherein the average pore diameter from the center to 30-50% of the sphere radius from the center is 10-25 nm; the average pore diameter from the position of 30-50% of the sphere radius from the sphere center to the position of 50-80% of the sphere radius from the sphere center is 20-40 nm; the average pore diameter from the sphere radius of 50-80% from the sphere center to the outer surface of the sphere is 40-60 nm, and the outer surface of the sphere contains macropores with the diameter of more than 100nm, and the corresponding pore volume accounts for 20-60% of the total pore volume.
The preparation method of the spherical step hole alumina comprises the following steps:
(1) Uniformly mixing the pseudo-boehmite PB-1 with the molding auxiliary materials to obtain powder A, uniformly mixing the pseudo-boehmite PB-2 with the molding auxiliary materials to obtain powder B, and uniformly mixing the pseudo-boehmite PB-2 with the molding auxiliary materials and the template agent to obtain powder C;
(2) Conveying the powder A into a sugar coating machine, spraying a peptizing agent to form balls, and stopping conveying the powder A when the average particle size of wet balls reaches a proper size; then conveying the powder B into a sugar coating machine, continuously spraying a peptizing agent to carry out balling, and stopping conveying the powder B when the average particle size of wet balls reaches a proper size; then the powder C is conveyed into a sugar coating machine, a peptizing agent is continuously sprayed to carry out balling, and when the average grain diameter of wet balls reaches a proper size, the balling is finished;
(3) And (3) carrying out health maintenance, drying and roasting on the obtained wet spheres to obtain the spherical step hole alumina.
Further, the pseudo-boehmite PB-1 and PB-2 in the step (1) can be commercial products, and can also be products prepared by any method in the prior art, such as an aluminum sulfate method, a carbonization method, an aluminum alkoxide hydrolysis method, a hydrothermal method and the like.
Furthermore, the pore volume of the pseudo-boehmite PB-1 is 0.8-1.2 mL/g, and the specific surface area is 200-350 m 2 And/g, the grain size d (120) is 8-20 nm; the pore volume of the pseudo-boehmite PB-2 is 1.0-1.5 mL/g, and the specific surface area is 80-200 m 2 And/g, the grain size d (120) is more than or equal to 25 and nm.
Further, in the step (1), the molding auxiliary material is selected from one or more of sesbania powder, starch, methyl cellulose, polyacrylamide and polycarboxylic acid, and the addition amount of the molding auxiliary material is 0.3-5% of the dry basis weight of the corresponding pseudo-boehmite.
Further, the template agent in the step (1) is one or more of high polymer powder such as polyethylene, polypropylene, polyvinyl chloride, polystyrene and polyurethane, and the addition amount of the template agent is 5-30% of the mass of the pseudoboehmite PB-2 dry basis.
Further, the peptizing agent in the step (2) is various peptizing agents commonly used in the art, and may be aluminum sol and/or silica sol, or may be inorganic acid and/or organic acid solution, wherein the mass concentration of the inorganic acid and/or the organic acid is 2-20%, the inorganic acid may be one or several of nitric acid, phosphoric acid, hydrochloric acid and sulfuric acid, preferably nitric acid, and the organic acid may be one or several of oxalic acid, acetic acid and citric acid.
Further, the temperature of the health maintenance in the step (3) is 10-40 ℃ and the time is 6-48 hours.
Further, in the step (3), the drying temperature is 50-150 ℃ and the drying time is 1-24 hours.
Further, the roasting temperature in the step (3) is 600-1000 ℃ and the time is 1-6 h.
The obtained spherical step hole alumina can be used as a residual oil hydrogenation catalyst carrier, in particular to an up-flow residual oil hydrotreating catalyst carrier.
The invention has the remarkable advantages that:
the pore canal structure of the alumina obtained in the invention is distributed in a step-like manner, and the macroporous structure of the surface layer can meet the requirements of the diffusion and mass transfer of macromolecular compounds, reduce the occurrence of reaction on the surface layer and avoid the blockage of removed metal and carbon deposit on the orifice; the mesoporous structure with the larger middle layer can effectively promote the reaction process, so that metal and carbon deposit are deposited in the catalyst, and meanwhile, compound molecules which become smaller after the metal is removed are further diffused to the inner layer; the mesoporous structure with smaller inner layer has larger specific surface area, can provide enough places for reaction, and the reacted product molecules can be rapidly diffused out due to the macroporous structure of the outer layer. Therefore, the alumina prepared by the invention has excellent diffusion performance, and is particularly suitable for being used as an up-flow residual oil hydrotreating catalyst carrier.
The preparation method provided by the invention is simple, the process flow is short, the thickness of each layer can be flexibly adjusted and easily controlled, and the preparation method is easy to be applied to industrial practice.
Drawings
FIG. 1 is a schematic diagram of the radial distribution of pore diameters of the spherical step pore alumina prepared by the present invention.
Detailed Description
A spherical step hole alumina, the preparation of which comprises the steps of:
(1) Uniformly mixing the pseudo-boehmite PB-1 with the molding auxiliary materials to obtain powder A, uniformly mixing the pseudo-boehmite PB-2 with the molding auxiliary materials to obtain powder B, and uniformly mixing the pseudo-boehmite PB-2 with the molding auxiliary materials and the template agent to obtain powder C;
(2) Conveying the powder A into a sugar coating machine, spraying a peptizing agent to form balls, and stopping conveying the powder A when the average particle size of wet balls reaches a proper size; then conveying the powder B into a sugar coating machine, continuously spraying a peptizing agent to carry out balling, and stopping conveying the powder B when the average particle size of wet balls reaches a proper size; then the powder C is conveyed into a sugar coating machine, a peptizing agent is continuously sprayed to carry out balling, and when the average grain diameter of wet balls reaches a proper size, the balling is finished;
(3) And (3) carrying out curing for 6-48 hours at 10-40 ℃, drying for 1-24 hours at 50-150 ℃, and roasting for 1-6 hours at 600-1000 ℃ to obtain the spherical step hole alumina.
Wherein, the molding auxiliary materials in the step (1) are selected from one or more of sesbania powder, starch, methyl cellulose, polyacrylamide and polycarboxylic acid, and the addition amount of the molding auxiliary materials is 0.3-5% of the weight of the corresponding pseudo-boehmite dry basis. The template agent is one or more of high polymer powder such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyurethane and the like, and the addition amount of the template agent is 5-30% of the mass of the pseudoboehmite PB-2 dry basis.
In order to make the contents of the present invention more easily understood, the technical scheme of the present invention will be further described with reference to the specific embodiments, but the present invention is not limited thereto.
Example 1
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 Mixing/g, crystal size d (120) of 15 nm) and 25 g sesbania powder uniformly to obtain powder A; 1000 g pseudo-boehmite PB-2 (pore volume of 1.2 mL/g, specific surface area of 120 m) was weighed 2 Mixing/g, crystal size d (120) 40 nm) and sesbania powder 25 g uniformly to obtain powder B; 1000 g pseudo-boehmite PB-2, 25 g sesbania powder and 70g polyethylene powder are weighed and mixed uniformly to obtain powder C1.
(2) Adding 20 g citric acid and 35 g nitric acid into 1000 g water, and stirring and mixing uniformly to obtain the peptizing agent P1.
(3) Conveying the powder A into a sugar coating machine, spraying a peptizing agent P1 to roll into balls, and stopping conveying the powder A when the average particle size of wet balls reaches 1.5 mm; then conveying the powder B into a sugar coating machine, continuously spraying a peptizer P1 to form balls, and stopping conveying the powder B when the average particle size of wet balls reaches 3.0 mm; and then the powder C1 is conveyed into a sugar coating machine and is continuously sprayed with a peptizer P1 for balling, and when the average grain diameter of wet balls reaches 4.0 mm, the balling is finished.
(4) The wet pellets were cured at room temperature 24 h, then dried at 80 ℃ for 6 h, and finally calcined at 650 ℃ for 4 h to give alumina sample S1.
Example 2
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 Mixing/g, crystal size d (120) of 15 nm) and 25 g sesbania powder uniformly to obtain powder A; 1000 g pseudo-boehmite PB-2 (pore volume of 1.2 mL/g, specific surface area of 120 m) was weighed 2 Mixing/g, crystal size d (120) 40 nm) and sesbania powder 25 g uniformly to obtain powder B; 1000 g pseudo-boehmite PB-2, 25 g sesbania powder and 80 g polyethylene powder are weighed and uniformly mixed to obtain powder C2.
(2) Adding 30 g citric acid and 35 g nitric acid into 980 g water, and stirring and mixing uniformly to obtain the peptizing agent P2.
(3) Conveying the powder A into a sugar coating machine, spraying a peptizing agent P2 for rolling to form balls, and stopping conveying the powder A when the average particle size of wet balls reaches 1.6 mm; then conveying the powder B into a sugar coating machine, continuously spraying a peptizing agent P2 for balling, and stopping conveying the powder B when the average grain diameter of wet balls reaches 2.8 mm; and then the powder C2 is conveyed into a sugar coating machine and is continuously sprayed with a peptizer P2 for balling, and when the average grain diameter of wet balls reaches 4.0 mm, the balling is finished.
(4) The wet pellets were left to stand at room temperature for 24 h, then dried at 80℃for 6 h, and finally calcined at 680℃for 4 h to give alumina sample S2.
Example 3
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 Mixing/g, crystal size d (120) of 15 nm) and 25 g sesbania powder uniformly to obtain powder A; 1000 g pseudo-boehmite PB-2 (pore volume of 1.2 mL/g, specific surface area of 120 m) was weighed 2 Mixing/g, crystal size d (120) 40 nm) and sesbania powder 25 g uniformly to obtain powder B; 1000 g pseudo-boehmite PB-2, 25 g sesbania powder and 90 g polyethylene powder are weighed and uniformly mixed to obtain powder C3.
(2) Adding 30 g citric acid and 40 g nitric acid into 980 g water, and stirring and mixing uniformly to obtain the peptizing agent P3.
(3) Conveying the powder A into a sugar coating machine, spraying a peptizing agent P3 to roll into balls, and stopping conveying the powder A when the average particle size of wet balls reaches 1.8 mm; then conveying the powder B into a sugar coating machine, continuously spraying a peptizing agent P3 for balling, and stopping conveying the powder B when the average grain diameter of wet balls reaches 3.2 mm; and then the powder C3 is conveyed into a sugar coating machine and is continuously sprayed with a peptizer P3 for balling, and when the average grain diameter of wet balls reaches 4.0 mm, the balling is finished.
(4) The wet pellets were left to stand at room temperature for 24 h, then dried at 80℃for 6 h, and finally calcined at 680℃for 4 h to give alumina sample S3.
Comparative example 1
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 /g, a crystal size d (120) of 15 nm) and 25 g sesbania powder,and mixing the materials uniformly to obtain powder A.
(2) Adding 20 g citric acid and 35 g nitric acid into 1000 g water, and stirring and mixing uniformly to obtain the peptizing agent P1.
(3) Powder A is conveyed into a sugar coating machine, a peptizer P1 is sprayed to roll into balls, and when the average grain diameter of wet balls reaches 4.0 mm, the balls are finished.
(4) The wet pellets were cured at room temperature for 24 h, then dried at 80℃for 6 h, and finally calcined at 650℃for 4 h to give alumina sample CS-1.
Comparative example 2
(1) 1000 g pseudo-boehmite PB-1 (pore volume of 1.0 mL/g, specific surface area of 220 m) was weighed 2 Mixing/g, crystal size d (120) of 15 nm) and 25 g sesbania powder uniformly to obtain powder A; 1000 g pseudo-boehmite PB-2 (pore volume of 1.2 mL/g, specific surface area of 120 m) was weighed 2 And/g, the crystal size d (120) is 40 nm) and 25 g sesbania powder are uniformly mixed to obtain powder B.
(2) Adding 20 g citric acid and 35 g nitric acid into 1000 g water, and stirring and mixing uniformly to obtain the peptizing agent P1.
(3) Conveying the powder A into a sugar coating machine, spraying a peptizing agent P1 for rolling to form balls, and stopping conveying the powder A when the average particle size of wet balls reaches 1.5 mm; then the powder B is conveyed into a sugar coating machine and is continuously sprayed with a peptizer P1 for balling, and when the average grain diameter of wet balls reaches 4.0 mm, the balling is finished.
(4) The wet pellets were cured at room temperature for 24 h, then dried at 80℃for 6 h, and finally calcined at 650℃for 4 h to give alumina sample CS-2.
1. The physicochemical properties of the aluminas obtained in the examples and comparative examples are shown in Table 1.
The method for measuring the average pore diameter of the alumina from the sphere center to different parts of the outer surface comprises the following steps: in the process of balling, when the spherical carrier grows to a certain particle size, taking out the sample, carrying out health preserving, drying and roasting, measuring the pore volume, the specific surface area and the average pore diameter of the sample by adopting a physical adsorption method, a mercury-pressing method and the like, and calculating the average pore diameter of different parts from the center of the sphere to the outer surface according to the relation that the total pore volume and the surface area of the sample are equal to the sum of all the parts.
Table 1 physicochemical properties of alumina samples obtained in examples and comparative examples
As can be seen from Table 1, the alumina prepared in the examples has an open pore structure with a stepped increase, and has a larger pore volume and pore diameter, and a considerable proportion of pore structures with a diameter of more than 100nm, wherein the pore diameter of the outer layer is obviously larger than that of the inner layer, and the pore is wider.
2. The alumina obtained in the examples and comparative examples was used as a carrier, and the same method was used to support the active metal, so that the corresponding catalysts all contained 5 wt% MoO 3 And 1 wt% NiO. The demetallization performance of the resulting catalyst was then evaluated on a 200 mL resid hydrogenation pilot plant. The sulfur content of the used raw material residual oil is 4.27 wt percent, the nitrogen content is 2870 ppm, the nickel content is 28 ppm, and the vanadium content is 85 ppm. The catalyst loading volume was 100 mL. The catalyst was presulfided by wet presulfiding prior to evaluation. The reaction conditions are as follows: the reaction temperature is 380 ℃, the hydrogen partial pressure is 15 MPa, and the liquid hourly space velocity is 1.0 h -1 The hydrogen oil volume ratio is 760. The process conditions for each catalyst were evaluated the same.
The content of nickel and vanadium in the oil before and after the reaction was determined by means of inductively coupled plasma emission spectrometry (ICP-OES) (see GB/T37160 for specific methods). The demetallization rate of each catalyst was calculated according to the following formula, and the evaluation results of the catalysts prepared from each alumina carrier are shown in table 2.
。
TABLE 2 determination of demetallization Rate of catalysts prepared with alumina from examples and comparative examples
The results in Table 2 show that the alumina supported catalyst prepared in the examples has higher demetallization activity and better activity stability.
The foregoing description is only of the preferred embodiments of the invention, and all changes and modifications that come within the meaning and range of equivalency of the claims are therefore intended to be embraced therein.

Claims (7)

1. 一种球形梯级孔氧化铝,其特征在于:以压汞法计,所述氧化铝的孔容为0.6~1.6mL/g,比表面积为80~250 m2/g,平均孔直径沿球体径向从球心到外表面呈阶梯式增大,其中,从球心至距离球心30-50 %球半径处的平均孔直径为10~25 nm;从距离球心30-50 %球半径处至距离球心50-80 %球半径处的平均孔直径为20~40 nm;从距离球心50-80 %球半径处至球体外表面的平均孔直径为40~60 nm,且球体外表面含有直径100 nm以上的大孔,其所对应的孔容占总孔容的20 %~60 %。1. A spherical stepped pore alumina, characterized in that: measured by mercury porosimetry, the pore volume of the alumina is 0.6~1.6mL/g, the specific surface area is 80~250 m2 /g, and the average pore diameter is along the The radial direction of the sphere increases stepwise from the center to the outer surface. Among them, the average hole diameter from the center to a distance of 30-50% of the radius of the sphere is 10~25 nm; The average pore diameter from the radius to 50-80% of the sphere's radius from the center of the sphere is 20-40 nm; the average pore diameter from 50-80% of the sphere's radius from the center to the outer surface of the sphere is 40-60 nm, and the sphere The outer surface contains large pores with a diameter of more than 100 nm, and their corresponding pore volume accounts for 20% to 60% of the total pore volume. 2.一种如权利要求1所述的球形梯级孔氧化铝的制备方法,其特征在于:包括如下步骤:2. A method for preparing spherical stepped pore alumina as claimed in claim 1, characterized in that it includes the following steps: (1)将拟薄水铝石PB-1与成型辅料混合均匀作为粉料A,将拟薄水铝石PB-2与成型辅料混合均匀作为粉料B,将拟薄水铝石PB-2与成型辅料及模板剂混合均匀作为粉料C;(1) Mix pseudo-boehmite PB-1 and molding auxiliary materials evenly as powder A, mix pseudo-boehmite PB-2 and molding auxiliary materials evenly as powder B, and mix pseudo-boehmite PB-2 Mix evenly with molding auxiliary materials and template agent to prepare powder C; (2)将粉料A输送到糖衣机中,喷洒胶溶剂进行成球,当湿球平均粒径达到适当大小时,停止输送粉料A;将粉料B输送到糖衣机中,继续喷洒胶溶剂进行成球,当湿球平均粒径达到适当大小时,停止输送粉料B;再将粉料C输送到糖衣机中,继续喷洒胶溶剂进行成球,当湿球平均粒径达到适当大小时,成球结束;(2) Transport powder A to the sugar-coating machine, spray glue to form balls. When the average particle size of the wet balls reaches the appropriate size, stop transporting powder A; transport powder B to the sugar-coating machine, and continue spraying glue. The solvent is formed into balls. When the average particle size of the wet ball reaches the appropriate size, stop conveying the powder B; then transport the powder C to the sugar coating machine, and continue to spray the peptizing agent to form the ball. When the average particle size of the wet ball reaches the appropriate size, hour, the ball formation ends; (3)将所得湿球经养生、干燥和焙烧后,得到所述球形梯级孔氧化铝。(3) After curing, drying and roasting the obtained wet balls, the spherical stepped pore alumina is obtained. 3. 根据权利要求2所述的球形梯级孔氧化铝的制备方法,其特征在于:步骤(1)中所述拟薄水铝石PB-1的孔容为0.8~1.2 mL/g,比表面积为200~350 m2/g,晶粒尺寸d(120)为8~20 nm;所述拟薄水铝石PB-2的孔容为1.0~1.5 mL/g,比表面积为80~200 m2/g,晶粒尺寸d(120)≥25 nm。3. The preparation method of spherical stepped pore alumina according to claim 2, characterized in that: the pore volume of pseudo-boehmite PB-1 in step (1) is 0.8~1.2 mL/g, and the specific surface area is 200~350 m 2 /g, and the grain size d(120) is 8~20 nm; the pore volume of the pseudo-boehmite PB-2 is 1.0~1.5 mL/g, and the specific surface area is 80~200 m 2 /g, grain size d(120)≥25 nm. 4. 根据权利要求2所述的球形梯级孔氧化铝的制备方法,其特征在于:步骤(1)中所述成型辅料选自田菁粉、淀粉、甲基纤维素、聚丙烯酰胺、多元羧酸中的一种或多种,其加入量为对应拟薄水铝石干基质量的0.3~5 %。4. The preparation method of spherical stepped pore alumina according to claim 2, characterized in that: the molding auxiliary materials in step (1) are selected from sesbania powder, starch, methylcellulose, polyacrylamide, polycarboxylic acid One or more acids are added in an amount of 0.3~5% corresponding to the dry basis mass of pseudo-boehmite. 5. 根据权利要求2所述的球形梯级孔氧化铝的制备方法,其特征在于:步骤(1)中所述模板剂为聚乙烯、聚丙烯、聚氯乙烯、聚苯乙烯、聚氨酯中的一种或多种,其加入量为拟薄水铝石PB-2干基质量的5~30 %。5. The preparation method of spherical stepped pore alumina according to claim 2, characterized in that: the template agent in step (1) is one of polyethylene, polypropylene, polyvinyl chloride, polystyrene, and polyurethane. One or more kinds, the addition amount is 5~30% of the dry basis mass of pseudoboehmite PB-2. 6. 根据权利要求2所述的球形梯级孔氧化铝的制备方法,其特征在于:步骤(3)中所述养生的温度为10~40℃,时间为6~48 h;所述干燥的温度为50~150 ℃,时间为1~24 h;所述焙烧的温度为600~1000 ℃,时间为1~6 h。6. The preparation method of spherical stepped pore alumina according to claim 2, characterized in that: the temperature for curing in step (3) is 10~40°C, and the time is 6~48 h; the temperature for drying The temperature is 50~150°C, and the time is 1~24 h; the roasting temperature is 600~1000°C, and the time is 1~6 h. 7.一种如权利要求1所述的球形梯级孔氧化铝在作为渣油加氢催化剂载体中的应用。7. The use of the spherical stepped pore alumina as claimed in claim 1 as a carrier for residual oil hydrogenation catalyst.
CN202310730494.8A 2023-06-20 2023-06-20 Spherical step hole alumina and preparation method and application thereof Active CN116835621B (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
CN202310730494.8A CN116835621B (en) 2023-06-20 2023-06-20 Spherical step hole alumina and preparation method and application thereof

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
CN202310730494.8A CN116835621B (en) 2023-06-20 2023-06-20 Spherical step hole alumina and preparation method and application thereof

Publications (2)

Publication Number Publication Date
CN116835621A true CN116835621A (en) 2023-10-03
CN116835621B CN116835621B (en) 2026-06-09

Family

ID=88169831

Family Applications (1)

Application Number Title Priority Date Filing Date
CN202310730494.8A Active CN116835621B (en) 2023-06-20 2023-06-20 Spherical step hole alumina and preparation method and application thereof

Country Status (1)

Country Link
CN (1) CN116835621B (en)

Cited By (1)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN117797792A (en) * 2023-12-19 2024-04-02 山西炬华新材料科技有限公司 A gradient pore distribution alumina carrier and its preparation method

Citations (9)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
EP0199394A2 (en) * 1985-04-26 1986-10-29 Shell Internationale Researchmaatschappij B.V. Process for producing wide-pore catalyst supports
CN103055947A (en) * 2011-10-21 2013-04-24 中国石油化工股份有限公司 Preparation method of alumina support
CN104646005A (en) * 2013-11-22 2015-05-27 中国石油天然气股份有限公司 Inferior heavy oil hydrodemetallization catalyst and preparation method thereof
CN111420710A (en) * 2020-04-29 2020-07-17 煤炭科学技术研究院有限公司 Alumina carrier with double-peak pore structure and preparation method thereof
CN114436304A (en) * 2020-10-19 2022-05-06 中国石油化工股份有限公司 Preparation method of spherical alumina carrier
CN114634194A (en) * 2020-12-16 2022-06-17 中国石油化工股份有限公司 Spherical three-dimensional through macroporous alumina and preparation method thereof
CN115888690A (en) * 2023-01-03 2023-04-04 中化泉州石化有限公司 Heavy oil hydrodemetallization catalyst for upflow reactor and preparation method thereof
CN115957740A (en) * 2023-01-03 2023-04-14 中化泉州石化有限公司 Heavy oil hydrotreating catalyst and preparation method thereof
CN116040663A (en) * 2021-10-28 2023-05-02 中国石油化工股份有限公司 A kind of alumina material with core-shell structure and preparation method thereof

Patent Citations (9)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
EP0199394A2 (en) * 1985-04-26 1986-10-29 Shell Internationale Researchmaatschappij B.V. Process for producing wide-pore catalyst supports
CN103055947A (en) * 2011-10-21 2013-04-24 中国石油化工股份有限公司 Preparation method of alumina support
CN104646005A (en) * 2013-11-22 2015-05-27 中国石油天然气股份有限公司 Inferior heavy oil hydrodemetallization catalyst and preparation method thereof
CN111420710A (en) * 2020-04-29 2020-07-17 煤炭科学技术研究院有限公司 Alumina carrier with double-peak pore structure and preparation method thereof
CN114436304A (en) * 2020-10-19 2022-05-06 中国石油化工股份有限公司 Preparation method of spherical alumina carrier
CN114634194A (en) * 2020-12-16 2022-06-17 中国石油化工股份有限公司 Spherical three-dimensional through macroporous alumina and preparation method thereof
CN116040663A (en) * 2021-10-28 2023-05-02 中国石油化工股份有限公司 A kind of alumina material with core-shell structure and preparation method thereof
CN115888690A (en) * 2023-01-03 2023-04-04 中化泉州石化有限公司 Heavy oil hydrodemetallization catalyst for upflow reactor and preparation method thereof
CN115957740A (en) * 2023-01-03 2023-04-14 中化泉州石化有限公司 Heavy oil hydrotreating catalyst and preparation method thereof

Non-Patent Citations (1)

* Cited by examiner, † Cited by third party
Title
侯瑞君;李敏香;吴钦;程俊涵;张春刚;孙克宁;: "梯度孔分布氧化铝载体的制备工艺研究", 精细石油化工, no. 02, 18 March 2018 (2018-03-18) *

Cited By (1)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN117797792A (en) * 2023-12-19 2024-04-02 山西炬华新材料科技有限公司 A gradient pore distribution alumina carrier and its preparation method

Also Published As

Publication number Publication date
CN116835621B (en) 2026-06-09

Similar Documents

Publication Publication Date Title
CN102441398A (en) A kind of preparation method of hydrodemetallization catalyst
CN100496738C (en) Alumina supporter possessing duplicate orifice, catalyst and preparation method
CN102441437A (en) Preparation method of macroporous alumina carrier and hydrodemetallization catalyst
CN103055947B (en) Preparation method of alumina support
CN108745392B (en) A kind of hydrodemetallization catalyst and preparation method thereof
CN115957740B (en) A heavy oil hydroprocessing catalyst and preparation method thereof
CN108654700A (en) Three peak pore size distribution Hydrodemetalation catalysts of one kind and preparation method thereof
CN111001411A (en) Residual oil hydrotreating catalyst and preparation method thereof
CN102861589A (en) High-activity hydrodemetallization catalyst and preparation method thereof
CN111375396A (en) Hydrotreating catalyst carrier, catalyst and preparation method thereof
CN115888690B (en) Heavy oil hydrodemetallization catalyst for up-flow reactor and preparation method thereof
CN104646009B (en) A kind of inferior heavy oil hydrogenation desulfurization catalyst and preparation method thereof
CN106914279A (en) Alumina carrier and its preparation method
CN115608371B (en) Eggshell type residuum hydrogenation catalyst and preparation method thereof
CN105749933B (en) A kind of preparation method of hydrogenation catalyst
CN104646008B (en) Hydrodesulfurization and demetallization catalyst for inferior heavy oil and preparation method thereof
CN116673019B (en) Upflow Residue Hydrogenation Catalyst and Its Preparation Method
CN103041869B (en) Preparation method of spherical catalyst carrier
CN114308090A (en) Hierarchical pore hydrotreating catalyst and preparation method thereof
CN104646005B (en) A kind of inferior heavy oil hydrogenation demetallization catalyst and preparation method thereof
CN103041837B (en) A kind of preparation method of spherical hydrogenation catalyst
CN103041820B (en) Preparation method of spherical hydrogenation catalyst
CN108404897A (en) A heavy oil hydrogenation catalyst carrier, its preparation method, a catalyst using it and a preparation method of the catalyst
CN1306456A (en) Process for producing spherical oxide particles
CN101239330A (en) Preparation method of microspherical catalyst carrier

Legal Events

Date Code Title Description
PB01 Publication
PB01 Publication
SE01 Entry into force of request for substantive examination
SE01 Entry into force of request for substantive examination
CB02 Change of applicant information
CB02 Change of applicant information

Country or region after: China

Address after: 362103 in QUANHUI Petrochemical Industrial Zone, Hui'an County, Quanzhou City, Fujian Province (Dongqiao town)

Applicant after: SINOCHEM QUANZHOU PETROCHEMICAL Co.,Ltd.

Applicant after: Sinopec Petrochemical Research Institute (Quanzhou) Co.,Ltd.

Address before: 362103 in QUANHUI Petrochemical Industrial Zone, Hui'an County, Quanzhou City, Fujian Province (Dongqiao town)

Applicant before: SINOCHEM QUANZHOU PETROCHEMICAL Co.,Ltd.

Country or region before: China

Applicant before: SINOCHEM QUANZHOU ENERGY TECHNOLOGY Co.,Ltd.

GR01 Patent grant
GR01 Patent grant